Shaping, intertextuality and summation in D.H. Lawrence's Last poems - Jones, Bethan Mari (1998)
This thesis, entitled ‘Shaping, Intertextuality and Summation in D. H. Lawrence's Last Poems’ , is the first full-length study of the poetry written by Lawrence in 1928-30, posthumously labelled ‘More Pansies’ and ‘Last Poems’ by Richard Aldington in 1932. My opening chapter discusses the characteristics of these two late poetry notebooks, challenging interpretations offered by Holly Laird and Christopher Pollnitz. I argue for the necessity of moving beyond an analysis limited to the consideration of poem sequences within a verse-book, or the evolution of individual poems through draft-stages. This conviction provokes a discussion of intertextual theory, in order to establish an approach which will facilitate the placing of Lawrence's late poetry in wider contexts. The resulting methodology aims to combine an empirical selection procedure in which intertexts are chosen according to key triggers or signposts within Lawrence-text, with an awareness that such selection is arbitrary, constituting an inevitable retrospective ordering.